Conplastic FVB/N-mt129S6/SvEvTac mice: A new tool for cancer research - Artiom Gruzdev; Wendy N. Jefferson; Thomas B. Hagler; Gregory J. Scott; Manas K. Ray; Ginger W. Muse; Rani S. Sellers; Carmen J. Williams (PLoS ONE, 2026)
FVB/N mice, which are commonly used for cancer studies, have accelerated onset of endometrial cancer following developmental estrogenic chemical exposure. These mice also have a polymorphism in the mitochondrial gene, mt-Atp8 , leading to increased production of reactive oxygen species. We hypothesized that this polymorphism contributes to the enhanced endometrial cancer phenotype in FVB/N mice. To test this idea, we generated conplastic FVB/N-mt129S6/SvEvTac mice (FVB/N nuclear genome; 129S6/SvEvTac mitochondria: FVB/N-mt129). The impact of 129S6 versus FVB/N mitochondrial genomes on endometrial cancer development following neonatal exposure to the xenoestrogen, diethylstilbestrol, was tested by comparing the cancer phenotypes of FVB/N mice to FVB/N-mt129 mice. There was no difference in cancer incidence regardless of mitochondria source, but cancer grade was higher in the conplastic strain. Additionally, while the FVB/N genetic background is considered non-permissive for generation of pluripotent mouse embryonic stem cells, blastocysts from the conplastic background readily generated mouse embryonic stem cell clones that supported gene editing in culture and subsequently generated germline competent chimeric founder mice. FVB/N-mt129 mice are a potentially powerful resource for generating germline competent embryonic stem cells with an FVB/N nuclear genome and for studying cancer phenotypes.